2017
DOI: 10.1016/j.anr.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experience of Thai Women with Alcohol Addiction

Abstract: Thai women who experience alcohol addiction are treated with gender-related double standards when trying to undo gender traditional roles. Their marginalization from family and society deepens making them even more vulnerable to the positive side effects of alcohol drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…In the cases of alcohol use disorders, some studies indicated that women face greater obstacles than males in seeking treatment for alcoholism. 21 , 22 In Thailand, it may be influenced by there is no specific intervention for women with alcoholism. 22 The healthcare service was provided in general services more than gender-specific services.…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of alcohol use disorders, some studies indicated that women face greater obstacles than males in seeking treatment for alcoholism. 21 , 22 In Thailand, it may be influenced by there is no specific intervention for women with alcoholism. 22 The healthcare service was provided in general services more than gender-specific services.…”
Section: Discussionmentioning
confidence: 99%
“…Nowhere is this complexity more apparent than in work specific to women. Woman, inclusive of cisgender, transgender and non-binary women, experience many concurrent challenges associated with substance abuse/addiction that can include childhood sexual abuse and other early life adversities, untreated mental health difficulties, parenting challenges, interpersonal violence and poverty (Andrews et al, 2019 ; Brown, 2008 ; Covington, 2008 ; Hanpatchaiyakul et al, 2017 ; Najavits, 2002 ; Poole & Greaves, 2012 ). One Canadian study of women who abused alcohol found that 90% of participants reported experiencing traumatic events, primarily childhood sexual abuse and using alcohol to self-medicate the painful feelings connected to these incidents (Brown, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Stressful life events and ineffective coping strategies were found to play a considerable role in patients' relapsing (20). Furthermore, alcohol addicts with familial problems, such as a failed marriage or conflicts with their children, were found to experience emotional guilt and shame which led to a withdrawal from social relations (21).…”
Section: Discussionmentioning
confidence: 99%